2015
DOI: 10.1016/j.rboe.2015.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Shockwave treatment for musculoskeletal diseases and bone consolidation: qualitative analysis of the literature

Abstract: Shockwave treatment is an option within orthopedics. The exact mechanism through which shockwaves function for treating musculoskeletal diseases is unknown. The aim of this study was to make a qualitative analysis on the effectiveness of shockwave treatment among patients with musculoskeletal pathological conditions and pseudarthrosis. Searches were conducted in the Cochrane Library, Medline and Lilacs databases. Thirty-nine studies that reported using shockwave treatment for musculoskeletal diseases were foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 35 publications
0
10
0
2
Order By: Relevance
“…Estudos demonstram efeitos diretos dessa terapia na estimulação de fatores cicatriciais. 53 54 Para as tendinopatias do Aquiles, trabalhos de moderada qualidade apresentaram o procedimento como portador de resultados confiáveis e de riscos muito baixos. Os ensaios clínicos de Costa et al, 30 Furia, 55 Rompe et al 56 e Rasmussen et al 57 Demonstraram bons resultados (80 a 88 pontos) e superioridade na comparação com terapias tradicionais (alongamento, manipulação, ultrassonografia), FE, e placebo.…”
Section: Tratamento Não-cirúrgicounclassified
See 1 more Smart Citation
“…Estudos demonstram efeitos diretos dessa terapia na estimulação de fatores cicatriciais. 53 54 Para as tendinopatias do Aquiles, trabalhos de moderada qualidade apresentaram o procedimento como portador de resultados confiáveis e de riscos muito baixos. Os ensaios clínicos de Costa et al, 30 Furia, 55 Rompe et al 56 e Rasmussen et al 57 Demonstraram bons resultados (80 a 88 pontos) e superioridade na comparação com terapias tradicionais (alongamento, manipulação, ultrassonografia), FE, e placebo.…”
Section: Tratamento Não-cirúrgicounclassified
“…Studies show that SWT direct effects the stimulation of healing factors. 53 54 For Achilles tendinopathies, moderate-quality studies showed that this procedure has reliable results and very low risks. Clinical trials from Costa et al, 30 Furia, 55 Rompe et al 56 and Rasmussen et al 57 presented good results (80–88 points) and superiority over traditional therapies (stretching, manipulation, ultrasound), eccentric strengthening and placebo.…”
Section: Introductionmentioning
confidence: 99%
“…Shock waves consist of high-energy, high-pressure mechanical sound pulses that are applied in a short time to a speci c part of the body [1][2][3]. The use of extracorporeal shock wave therapy (ESWT) in medicine began in 1980 with lithotripsy in urolithiasis [1].…”
Section: Introductionmentioning
confidence: 99%
“…The use of extracorporeal shock wave therapy (ESWT) in medicine began in 1980 with lithotripsy in urolithiasis [1]. Later studies demonstrated the bene ts of ESWT in bone ailments such as delayed fracture healing and pseudoarthrosis [1][2][3][4]. The osteogenic effect of ESWT is well de ned in medical literature due to the fact that the activation of the integrincytoskeleton-nucleus protein system acts in the conversion of the mechanical to biological stimulus and promotes the release of growth factors [5].…”
Section: Introductionmentioning
confidence: 99%
“…Dentre as opções terapêuticas para o tratamento da FP, o método de escolha geralmente é o tratamento conservador, pois, tem se obtido resultados satisfatórios em cerca de 90% dos pacientes, reduzindo ou abolindo a dor, restaurando a função mecânica da fáscia plantar e melhorando a marcha 1, 7,8 . Nesse cenário, uma das técnicas que vem sendo cada vez mais utilizada para a forma crônica da FP é a terapia por ondas de choque (TOC), que surgiu no Brasil em 1998 como uma nova tecnologia utilizada, tendo como objetivo promover a cicatrização do tecido inflamado 9 .…”
Section: Introductionunclassified